Aging and insulin signaling differentially control normal and tumorous germline stem cells. Issue 1 (3rd December 2014) - Kao, Shih‐Han; Tseng, Chen‐Yuan; Wan, Chih‐Ling; Su, Yu‐Han; Hsieh, Chang‐Che; Pi, Haiwei; Hsu, Hwei‐Jan
Summary Aging influences stem cells, but the processes involved remain unclear. Insulin signaling, which controls cellular nutrient sensing and organismal aging, regulates the G2 phase of Drosophila female germ line stem cell (GSC) division cycle in response to diet; furthermore, this signaling pathway is attenuated with age. The role of insulin signaling in GSCs as organisms age, however, is also unclear. Here, we report that aging results in the accumulation of tumorous GSCs, accompanied by a decline in GSC number and proliferation rate. Intriguingly, GSC loss with age is hastened by either accelerating (through eliminating expression of Myt1, a cell cycle inhibitory regulator) or delaying (through mutation of insulin receptor (dinR) GSC division, implying that disrupted cell cycle progression and insulin signaling contribute to age‐dependent GSC loss. As flies age, DNA damage accumulates in GSCs, and the S phase of the GSC cell cycle is prolonged. In addition, GSC tumors (which escape the normal stem cell regulatory microenvironment, known as the niche) still respond to aging in a similar manner to normal GSCs, suggesting that niche signals are not required for GSCs to sense or respond to aging. Finally, we show that GSCs from mated and unmated females behave similarly, indicating that female GSC–male communication does not affect GSCs with age. Our results indicate the differential effects of aging and diet mediated by insulin signaling on the stem cell division cycle, highlight the complexity of the regulation of stem cell aging, and describe a link between ovarian cancer and aging.